Analisis Framing Pemberitaan Pertemuan Agus Harimurti Yudhoyono dan Puan Maharani Pada Media Televisi Tvone dan Metrotv - Farhansyah, Muhammad (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
Framing is the process of framing or ideas for a media in conveying news to the public with different characteristics from each mass media to attract particular interest to the public who will see or consume the news conveyed by the mass media. Mass media is a forum for the public to find out about developments in news information circulating. Mass media can be interpreted as a means of communication in the form of media to publish and convey news to the public in narrative form such as online or print media, in audio or sound form such as radio, or audio visual such as television. This research explains how tvOne and METROTV framed the news about the meeting of Agus Harimurti Yudhoyono and Puan Maharani which was published via the tvOne and METROTV YouTube channels. The aim of this research is to find out how tvOne and METROTV think in framing news. This research uses a descriptive method with a qualitative approach using Robert Entmant's framing theory model. The results of the research refer to Robert Entmant's framing theory, where framing is divided into four elements, namely Define problem, Diagnose cause, Make moral judgment, Treatment recommendation. This research carried out a descriptive research method with a qualitative approach that describes framing analysis into four elements of theory Robert Entmant.